Inductively Coupled Modular Battery System for Electric Vehicles - Kandasamy, Karthik (2016)
This study proposes two novel modularised battery systems capable of controlling the power of each module independently, and with inductive interface for convenient battery swapping. The proposed systems aid in overcoming the limitations such as unavailability of electric vehicle (EV) due to battery pack fault and lengthy battery recharging time which largely hampers the adoption of EVs for personal transportation. The proposed systems consist of a plurality of battery modules which are wirelessly coupled to the EV through inductive power transfer technology. The proposed systems are described in detail, and models are presented to analyse their steady-state behaviours. A design guideline for a 24 kWh 80 kW battery micro-pack system is discussed. Performances of the proposed topologies are investigated using simulations. To demonstrate the applicability, prototype systems of 1.5 kW are implemented and tested under various operating conditions. Results convincingly indicate that the proposed systems improve the vehicle's availability under fault condition.